2019
DOI: 10.1111/aos.14197
|View full text |Cite
|
Sign up to set email alerts
|

Variance components for PIMD‐2π estimation of the optic nerve head and consequences in clinical measurements of glaucoma

Abstract: Purpose To estimate the sources of variation for Pigment epithelium central limit‐Inner limit of the retina Minimal Distance averaged over 2π (PIMD‐2π), and further to analyse their consequences for clinical measurements of glaucoma. Methods Forty subjects with early to moderate stage glaucoma were included. Three SD‐OCT volumes of the optic nerve head (ONH) were captured at two occasions. Each volume was segmented three times for PIMD‐2π. The magnitude of the sources of variation for PIMD‐2π measurements was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In our original publications (Sandberg Melin et al, 2019a, 2019b), PIMD was estimated as the spatial distance between OPCL and IRCP. Due to the limitation in the spatial resolution, often, the same IRCP corresponded to consecutive OPCL coordinates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our original publications (Sandberg Melin et al, 2019a, 2019b), PIMD was estimated as the spatial distance between OPCL and IRCP. Due to the limitation in the spatial resolution, often, the same IRCP corresponded to consecutive OPCL coordinates.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that there is no difference in efficiency between PIMD-2π and PIMA-2π at 0.95 specificity considering averages among subjects (Söderberg et al, 2022). The lack of difference is probably due to substantial variability among individuals (Sandberg Melin et al, 2019b). Within-subject comparison may result in different efficiencies.…”
Section: Discussionmentioning
confidence: 99%